Real-Time Neuron Detection and Neural Signal Extraction Platform for Miniature Calcium Imaging - Lee, Yaesop; Xie, Jing; Lee, Eungjoo; Sudarsanan, Srijesh; Lin, Da-Ting; Chen, Rong; Bhattacharyya, Shuvra S. (Frontiers in Computational Neuroscience, 2020)
Real-time neuron detection and neural activity extraction are critical components of real-time neural decoding. In this paper, we propose a novel real-time neuron detection and activity extraction system using a dataflow framework to provide real-time performance and adaptability to new algorithms and hardware platforms. The proposed system was evaluated on simulated calcium imaging data, calcium imaging data with manual annotation, and calcium imaging data of the anterior lateral motor cortex. We found that the proposed system accurately detected neurons and extracted neural activities in real-time without any requirement for expensive, cumbersome or special-purpose computing hardware. We expect that the system enables cost-effective, real-time calcium imaging based neural decoding, leading to precise neuromodulation.